PELATIHAN PEMBUKUAN SEDERHANA UNTUK PENINGKATAN PENDAPATAN USAHA KECIL DI JEMAAT GPM SILO KLASIS KOTA AMBON - Grace Persulessy; Nicoline Hiariej; Beatrix A Talakua (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Small businesses need skills to make financial records so that they can increase family income. This service activity aims to provide knowledge in carrying out financial records for small businesses in the GPM Silo Klasis in Ambon City. The method used is lecture, practice and evaluation. The result of this activity is that the training participants can make financial records for small businesses. berisi tentang isu dan fokus pengabdian, tujuan pengabdian, metode/pendekatan/strategi riset pengabdian, dan hasil pengabdian masyarakat (maksimal 150 kata). (Cambria, size 12 font Italic)